1992
DOI: 10.1088/0268-1242/7/1a/025
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of D defects in silicon single crystals by preferential etching and effect on gate oxide integrity

Abstract: A method for revealing point defects in silicon single crystals has been investigated. D or A defects could be revealed by a Preferential etching technique using Secco's etchant. Wedge-shaped flow patterns and etch pits were recognised in the D and A regions, respectively. The flow patterns were so characteristic that the D region could be distinguished very easily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(50 citation statements)
references
References 2 publications
1
49
0
Order By: Relevance
“…The effect of N doping on the apparently complete suppression of the D defect region was first reported by Abe and Harada using X-ray topography of Cu decorated FZ Si [17]. Yamagishi et al saw the same result using the Secco etch technique [4]. This effect was also seen with the elimination of COPS and FPDs and an increase in GO1 [4,.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The effect of N doping on the apparently complete suppression of the D defect region was first reported by Abe and Harada using X-ray topography of Cu decorated FZ Si [17]. Yamagishi et al saw the same result using the Secco etch technique [4]. This effect was also seen with the elimination of COPS and FPDs and an increase in GO1 [4,.…”
Section: Discussionmentioning
confidence: 67%
“…Yamagishi et al saw the same result using the Secco etch technique [4]. This effect was also seen with the elimination of COPS and FPDs and an increase in GO1 [4,. In 0-free Si, Ni pairs having CU, symmetry are the dominant defect [18].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Thus, their structural characterizations have been the subject of intense theoretical and experimental investigations. [3][4][5] Normally, when the wafer growth rate is about 1.0 mm/ mim or higher, grown-in defects called crystal originated particles (COPs), of about 0.1 µm in size and 10 6 /cm 3 in density, are formed. 6) Nakai et al 7) has reported that when the growth rate is about 0.4 mm/min or lower, dislocation clusters of 10 6 /cm 3 density are observed in CZ Si wafers.…”
Section: Introductionmentioning
confidence: 99%